Analisis Break Even Point pada Waralaba Sabana Fried Chicken Outlet Jatirahayu, Bekasi - Siti Juriah; Rudeva Juniawaty (LITERATUS, 2020)
This research was conducted with the aim of knowing the level of sales that must be maintained so as not to experience a loss and knowing the minimum number of sales that must be achieved at the planned profit target. The method used in this research is a quantitative method, namely the collection of data such as cost data, income data and sales data, classifying costs and then calculating the break-even point and the rupiah break-even point. Data were collected through interviews. The result of the research is that Sabana Jatirahayu Outlet can experience a return on investment if it is able to sell 4,922 pieces of chicken meat in one month, at the sale of chicken, for example 5,000 pieces of chicken meat, Sabana Jatirahayu outlet has benefited because fixed costs have been covered by the previous sale of 4,922 pieces of chicken. BEP will occur when the sales figure has reached Rp. 49,223,535 after passing the amount, for example in the figure of Rp. 50,000,000, - then the Sabana Jatirahayu outlet is said to be a return on investment so that subsequent sales can generate profits within 140 days (4 months).